Editorial - González-Campo, Carlos Hernán (Cuadernos de Administración, 2020)
This 68th issue of the journal Cuadernos de Administración corresponds to the September-December 2020 period and gives closure to volume 36 on its 44th year. Twenty-twenty was a different year in many respects and with regards to past editorial processes, as it was faced with limitation and challenges associated with situation-specific constraints, new issues, and problems to be addressed, such as research in the sciences of administration, among other areas of the knowledge. As with past issues, the 16 papers published in issue 68 come from the previous months’ call, whose authors - from several countries and different regions of Colombia - entrusted their manuscripts to our editorial process. I thank our peer reviewers who supported us through their experience and expertise in assessing each paper for what we believe is an objectivity-based academic dialogue that seeks to recognize the quality of the scientific output proposed for each issue of Cuadernos de Administración. The first three papers in this issue are “Development of typical vacuum-packed and frozen Boyaca soups”, “Territorial Governance: A bibliometric analysis” and “University reports in Colombia: a contribution to accountability” The first paper’s authors study gastronomy and tourism in the department of Boyacá, Colombia, and their production processes to facilitate product handling and increase their offer to tourists. The second one is a bibliometric literature study analyzing territorial governance by analyzing papers from the Web of Science. The third paper presents the current state of accountability in Colombian public universities through research carried out analyzing university reports using the content analysis method. The second group of papers includes those entitled “The effect of human resource management practices and innovation: Colombian small and medium-sized enterprises”, “Quality Assessment in the Context of Banking Services” and “Performance appraisal: an experience between recognition and contempt” The first paper of that group accounts for the research carried with SME 492 managers in Cali, Bogotá, and Medellín on human resources management practices and their innovation effect. The second paper uses theoretical systematization to approach the quality assessment of services, banking services in this case, from a critical standpoint. The third article is a case study that uses qualitative interviews on a group of workers from a Colombian company in the energy generation and distribution sector. It examined the recognition or contempt experienced by and evidenced in the workers’ discourse after undergoing a performance appraisal designed under the Strategic Human Resources Management (SHRM) logic. The third group of articles consists of those entitled “A comprehensive tax reform under OECD parameters for Colombia”, “Updating the strategic framework for the Spanish port system using a SWOT analysis” and “Correlating affective commitment with prosocial behavior: Does it matter to perceive that work has meaning?” The first one studies tax reforms in Colombia, the orientation of these, and identifies structuring-related problems. The second paper uses the SWOT analysis and benchmarking to analyze the Spanish port system. Finally, in the third paper, a study was conducted on 144 professional employees across various Colombian industries to analyze their prosocial behavior and attitudes in different organizational environments and under varying management practices, which may or may not promote prosocial behavior. “Absenteeism at work, remuneration, and equity: a confusing relationship”, “The role of family dynamics and culture in the psychological ownership of family shareholders in family businesses” and “Prospective and its valuation in public policy of two regional development strategies in Chile” are the papers that follow in this number. The first paper presents the results of a study conducted in a higher education institution that analyzes the relationship between absenteeism, workers’ compensation, and equity variables using statistical methods and based on 840 inputs. The second article studies 14 cases of Colombian and 5 Finns shareholders using qualitative and exploratory methods to analyze the role of family dynamics and culture in developing psychological ownership in family shareholders. The third article studies Chilean public officials’ perception of prospective from a qualitative approach, which is considered a tool for public policies in two regional development strategies. The following two papers are “Social commitment in organizations: a look at Universidad del Valle“ and “Current Challenges of the Social Function of Accounting” The first of the aforementioned papers’ authors study social commitment in a case study applied to the Universidad del Valle through interviews with officials and using content analysis on the Outreach Office’s management reports and the University’s Strategic Development Plans. The second article aims to determine potential social costs and financial statements’ models for social accounting. The last group of articles includes “Strengths and opportunities of sustainable entrepreneurship in Colombia” and “Institutional isomorphism in IPSAS adoption” The first case is an analysis of the strengths and opportunities of sustainable entrepreneurship in Colombia based on the review of papers published in the Colombian context, as available in the primary databases (national journals and university repositories were also included). The last article presents the results of a systematic literature review to study institutional isomorphism in governments’ implementation of IPSAS into their accounting model. The publication of Universidad del Valle’s Faculty of Administration’s 68th issue of Cuadernos de Administración consolidates us as a means of dissemination for scientific knowledge in that area. Twenty twenty-one will see our 45th year of publication, for which there will be a thematic issue on Circular Economy, with the support of HEC Montreal and the ITESM. In that anniversary framework, the first issue will present an analysis of these 45 years’ publications, among other activities. Once again, we thank each of the authors of these 16 papers and the peer reviewers who supported our editorial process, always bearing in mind that each article’s content is its authors’ responsibility. We hope that this issue will contribute to our readers’ academic work and that it will drive our research, reflections, or reviews in the sciences of administration.